Use of sludge from a conventional drinking water treatment process as a coagulant and adsorbent for the treatment of wastewater (2024)
ABSTRACT : Global water consumption has increased in recent years and continues to rise due to population growth, economic development, and shifting consumption patterns. Meeting the demand for drinking water necessitates designing and constructing drinking water treatment facilities (DWTP), inevitably leading to the generation of water treatment sludges (WTS) as by-products of the treatment processes. Consequently, thousands of tons of WTS are generated daily worldwide, and this waste generation is expected to increase in the coming decades. Therefore, exploring alternatives for managing WTS within the circular economy context is fundamental. This thesis centres on the reuse and recovery of materials WTS for wastewater treatment, aiming to apply circular economy principles in the water sector. The document comprises seven chapters. The first chapter introduces the thesis, including objectives and structure. The second chapter focuses on quantifying and characterising WTS generated in a DWTP. The third chapter evaluates the reuse of WTS to produce adsorbents studied for removing the antibiotic azithromycin (AZT), an emerging water contaminant. Chapters four and five assess the enhancement of primary domestic wastewater (WW) treatment using recovered coagulants (RCs) from WTS, along with unmodified and chemically modified WTS (RSs), respectively. Chapter six explores the reuse of WTS for producing nitrogen-doped (N-doped) catalysts, which are examined in carbocatalysis to activate peroxymonosulfate (PMS) for degrading the pollutant methyl orange (MO) in water. Finally, the seventh chapter offers a final discussion and recommendations for future research within the scope of this study. The results showed that the characterised WTSs have potential uses in wastewater treatment as coagulants (or for the recovery of coagulants) and as raw materials for generating adsorbents. In primary WW treatments, recovered coagulant and reactive sludge from the wet WTS with sulfuric acid showed better turbidity removal. They were selected as the optimal treatments showing high suspended solids, organic matter, and phosphorous removals. In tertiary treatment in a municipal WW, adsorbent derived from the calcination (at 500 °C) of WTS generated under low turbidity in the DWTP demonstrated substantial AZT removal efficiency. Additionally, the N-doped catalyst generated from WTS presented the best synergy between the absorption and oxidation processes, leading to higher MO removal by oxidation. These applications offer a valuable circular economy solution in the water sector, simultaneously valorising waste from the drinking water process and contributing to achieving Sustainable Development Goals 11 (Responsible Consumption and Production) and 6 (Clean Water and Sanitation).